Integration of Islamic Values in Learning Methods: Building Character and Spirituality in the Digital Era - Juwairiyah, Juwairiyah; Fanani, Zainuddin (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
Islamic education is more than just a knowledge transfer process; it is a profound effort to shape individual character and spirituality. In this context, learning methods are crucial in applying religious and moral values in daily life. This research employs a qualitative approach through literature analysis, demonstrating that integrating Islamic values as a fundamental basis for forming the personalities of the young Muslim generation is vital. Learning methods that focus on the Quran, Hadith, and scientific literature not only enable students to deeply understand religious teachings but also to develop strong moral and spiritual character. The role of technology in Islamic education is also discussed, highlighting the use of online platforms and applications that broaden access and deepen understanding of Islamic values in today's digital era. The implications of this research for educators emphasize the need for developing teaching methods aligned with Islamic values, while for education policymakers, it indicates the necessity of inclusive policies that accommodate moral values within the national education system. These steps are expected to foster a more ethical society that respects religious values in various aspects of life, in line with the holistic and sustainable vision of Islamic education. Keywords: Islamic Education, Learning Methods, Character, Technology.